Second Primary Gynecologic Cancers After Breast Cancer in Turkish Women. Issue 4 (1st April 2009) - Gulhan, Ibrahim; Eser, Sultan; Yakut, Cankut; Bige, Ozgur; Ilhan, Enver; Yildirim, Yusuf; Saygili, Ugur
Abstract : Objectives: To determine the risk of gynecologic cancers among women with previous breast cancer. Methods: A population-based longitudinal study was conducted using the Izmir cancer registry center's data on 6356 breast cancer patients diagnosed in the period 1992 to 2006. Standardized incidence ratios (SIR) and absolute excess risks (AER) were calculated. Results: In total, 88 (1.3%) women developed a second primary cancer (other than second primary breast cancers) versus 49.8 expected (SIR, 1.76; 95% confidence interval [CI], 1.43-2.2; AER, 86.9/100.000 patients/y) and 33 of 88 (37.5%) women developed gynecologic cancer (21 endometrial, 8 ovarian, and 4 cervical) versus 8.8 expected (SIR, 4.03; 95% CI, 2.8-5.7; AER, 48.2/100.000 patients/y). High SIR and AER were observed for uterine (SIR, 2.2; 95% CI, 1.5-2.7; AER, 35/100.000 patients/y), ovarian (SIR, 3.63; 95% CI, 1.6-7.2; AER, 12.2/100.000 patients/y), and cervical cancer (SIR, 1.68 95% CI: 0.46-4.3; AER, 2.2/100, 000 patients/y). Conclusions: Our data show that women with previous breast cancer have an elevated risk of developing a second primary gynecologic cancer compared with the general population. These patients should be followed up frequently.